Microneedles: quick and easy delivery methods of vaccines - Kwon, Ki Mun (Clin Exp Vaccine Res, 2017)
Vaccination is the most efficient method for infectious disease prevention. Parenteral injections such as intramuscular, intradermal, and subcutaneous injections have several advantages in vaccine delivery, but there are many drawbacks. Thus, the development of a new vaccine delivery system has long been required. Recently, microneedles have been attracting attention as new vaccination tools. Microneedle is a highly effective transdermal vaccine delivery method due to its mechanism of action, painlessness, and ease of use. Here, we summarized the characteristics of microneedles and the possibilities as a new vaccine delivery route.